2008
DOI: 10.1103/physrevd.77.034013
|View full text |Cite
|
Sign up to set email alerts
|

QCD coupling below 1 GeV from the quarkonium spectrum

Abstract: In this paper we extend the work synthetically presented by M. Baldicchi, A. V. Nesterenko, G. M. Prosperi, D. V. Shirkov, and C. Simolo [Phys. Rev. Lett. 99, 242001 (2007)] and give theoretical details and a complete set of numerical results. We exploit calculations within a Bethe-Salpeter (BS) formalism adjusted for QCD, in order to extract an experimental strong coupling exp s Q 2 below 1 GeV by comparison with the meson spectrum. The BS potential follows from a proper ansatz on the Wilson loop to encode c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
44
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 74 publications
11
44
1
Order By: Relevance
“…The running coupling must go to zero like the fourth power of momentum being this in agreement with lattice computations as shown by Boucaud et al [17] but as also seen from experiments as shown by Prosperi et al [18,19,20]. These latter results on the running coupling give a strong clue that Yang-Mills theory is trivial as happens for the scalar field theory.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The running coupling must go to zero like the fourth power of momentum being this in agreement with lattice computations as shown by Boucaud et al [17] but as also seen from experiments as shown by Prosperi et al [18,19,20]. These latter results on the running coupling give a strong clue that Yang-Mills theory is trivial as happens for the scalar field theory.…”
supporting
confidence: 72%
“…For this to work we need to go to Euclidean momenta and fix m 0 in eq. (20). The result is presented in Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In Ref. [27], the authors obtained a first principal Bethe-Salpeter equation, and then reduced it to the eigenvalue equation for the square mass operator [26][27][28][29][30] by means of a three dimensional reduction…”
Section: Qssementioning
confidence: 99%
“…As applying the formula (1) to fit the bottomonia and charmonia, the results are excellent. In the present work, we use the quadratic form of the spinless Salpeter-type equation (QSSE) [26][27][28][29][30][31][32][33] to discuss the Regge trajectories for the mesons consisting of different quarks. We find that the obtained formula can be written in the same form as the Regge trajectories in Eq.…”
Section: Introductionmentioning
confidence: 99%